The relationship between external debt and agriculture GDP growth in Ghana: an ARDL cointegrating bound testing approach - Ernest Sogah; Joseph K. Tuffour; John Kwaku Mensah Mawutor; Freeman Christian Gborse (Cogent Economics & Finance, 2024)
AbstractThe relationship between external debt and agriculture productivity is a topic of significant importance in developing economies. Agriculture is a fundamental sector in these economies, often providing livelihoods for a substantial portion of the population. External debt, on the other hand, is a commonly used financing mechanism for economic development. Understanding how these two variables interact is crucial for policymakers because it has far-reaching implications for food security, poverty reduction, and overall economic stability. The main objective of this study is to establish the relationship between external debt and agricultural GDP growth in Ghana. The Augmented Dickey Fuller and Phillips-Parron tests and the autoregressive distributed lag (ARDL) to co-integration bound testing approach were employed for the econometrics analysis from 1980 to 2019. The study revealed a direct and significant effect of external debt on agricultural GDP growth in Ghana. This implies that external funds were optimally channeled and used to stimulate agricultural output. The results indicate that external debt servicing has a positive effect on agricultural GDP growth, suggesting that Ghana is capable of always fulfilling its debt obligation. The study’s key contributions are that the paper is the first to investigate the link between external debt and agricultural GDP growth in Ghana. Furthermore, the study has indicated that external debt is a catalyst to augment agriculture GDP growth in Ghana. Finally, we investigate the long -term effect of the variables of interest on agricultural GDP growth.